2008
DOI: 10.1152/jn.00053.2008
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Behavior of Swimming C. elegans Analyzed by Measuring Motile Responses to Temporal Variations of Odorants

Abstract: Luo L, Gabel CV, Ha H-I, Zhang Y, Samuel AD. Olfactory behavior of swimming C. elegans analyzed by measuring motile responses to temporal variations of odorants. J Neurophysiol 99: 2617-2625, 2008. First published March 26, 2008 doi:10.1152/jn.00053.2008. Caenorhabditis elegans responds to chemical cues using a small number of chemosensory neurons that detect a large variety of molecules in its environment. During chemotaxis, C. elegans biases its migration in spatial chemical gradients by lengthening (/short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 30 publications
3
53
0
2
Order By: Relevance
“…1c). These results indicate that the odorant preference of C. elegans alters depending on the concentration of various odorants, consistent with the previous reports that high concentrations of several odorants caused avoidance behaviour 8,11,12 . Because of the abundant knowledge about isoamyl alcohol based on laser ablation experiments, calcium imaging experiments and others, we focused on isoamyl alcohol in this study 8,13 .…”
Section: Odour Concentration-dependent Preference Shift In C Eleganssupporting
confidence: 92%
See 1 more Smart Citation
“…1c). These results indicate that the odorant preference of C. elegans alters depending on the concentration of various odorants, consistent with the previous reports that high concentrations of several odorants caused avoidance behaviour 8,11,12 . Because of the abundant knowledge about isoamyl alcohol based on laser ablation experiments, calcium imaging experiments and others, we focused on isoamyl alcohol in this study 8,13 .…”
Section: Odour Concentration-dependent Preference Shift In C Eleganssupporting
confidence: 92%
“…ODR-3 was previously reported to be expressed in five pairs of sensory neurons, AWA, AWB, AWC, ASH and ADF 20 . Among these neurons, AWB and ASH sensory neurons are known to mediate avoidance of volatile odorants [9][10][11][12] . Avoidance defects of the odr-3 mutants were rescued by either AWB-or ASH-specific expression of odr-3 cDNA (Fig.…”
Section: A Gα Odr-3 Mediates Bidirectional Behavioural Responsesmentioning
confidence: 99%
“…It was recently demonstrated that C. elegans also respond to a decrease in the concentration of odorants by increasing the frequency of reversals (Chalasani et al, 2007;Luo et al, 2008). These observations are consistent with the assumption that odorant chemotaxis is also achieved by the pirouette strategy.…”
Section: A Novel Mechanism For Chemotaxissupporting
confidence: 79%
“…In fact, in addition to the result of tracking analyses (PierceShimomura et al, 1999), various behavioral analyses have supported this model: by using glued animals and semirestrained animals, it was shown that worms show a reversal response to a decrease in salt concentration (Dusenbery, 1980;Miller et al, 2005). Similar reversal responses were detected for odorants (Chalasani et al, 2007;Luo et al, 2008). Behavioral analyses of the temperature response also supported the pirouette model (Ryu and Samuel, 2002).…”
Section: Discussionmentioning
confidence: 87%
“…1d), a defect which was fully rescued by introducing the odr-10 and odr-7 genomic transgenes, respectively (Supplementary Figs S3,S4). The ceh-36 gene is required for the development and function of AWC neurons 10,11 , while the odr-10 gene is normally expressed exclusively in AWA neurons under the control of odr-7 and encodes a G-protein-coupled receptor that detects diacetyl [7][8] . These data indicate that diacetyl induces feeding facilitation mainly via sensing through the AWA sensory neurons.…”
mentioning
confidence: 99%